Developmentally Regulated Spontaneous Activity in the Embryonic Chick Retina - Wong, Wai T. (J Neurosci, 1998)
Even before birth and the onset of sensory experience, neural activity plays an important role in shaping the vertebrate nervous system. In the embryonic chick visual system, activity in the retina before vision has been implicated in the refinement of retinotopic maps, the elimination of transient projections, and the survival of a full complement of neurons. In this study, we report the detection of a physiological substrate for these phenomena: waves of spontaneous activity in the ganglion cell layer of the embryonic chick retina. The activity is robust and highly patterned, taking the form of large amplitude, rhythmic, and wide-ranging waves of excitation that propagate across the retina. Activity waves are most prominent and organized between embryonic days 13–18, coinciding with the developmental period during which retinal axons refine their connections in their targets. The spatial and temporal features of the patterns observed are consistent with the role of activity patterns in shaping eye-specific projections and retinotopic maps but inconsistent with the hypothesis that they specify lamina-specific projections in the tectum. Antagonists of glutamatergic and glycinergic transmission and of gap junctional communication suppress spontaneous activity, whereas antagonists to GABAergic transmission potentiate it. Based on these results, we propose that spontaneous activity in the ganglion cells is regulated by chemical inputs from both bipolar and amacrine cells and by gap junctional coupling involving ganglion cells.